(untitled) (Rome, 2005)
Contents: Scope and purpose; National planning coordination; Operational capability; Early warning; Disease surveillance; Recovery from an emergency disease...
Keywords: Fishes,Nuôi thủy hải sản; Diseases,Bệnh; Asia,Châu Á